Archetyp bohatera w powieści Olega Pawłowa „Opowieść Skarbu Państwa” - Kryłowa, Snieżana (Studia Rossica Posnaniensia, 2011)
In the article, basic features of the main hero of the story The state fairy tale captain Khabarov are being analysed. It’s also proved that the story became a support for overcoming the spiritual chaos for the writer during the epoch of disintegration of the 1990s.